Impact of rail pressure and biodiesel fueling on the particulate morphology and soot nanostructures from a common-rail turbocharged direct injection diesel engine. (February 2016) - Ye, Peng; Sun, Chenxi; Lapuerta, Magin; Agudelo, John; Vander Wal, Randy; Boehman, Andre L; Toops, Todd J; Daw, Stuart
An investigation of the impact of rail pressure and biodiesel fueling on exhaust particulate agglomerate morphology and primary particle (soot) nanostructure was conducted with a common-rail turbocharged direct injection diesel engine. The engine was operated at steady state on a dynamometer running at moderate speed with both low (30%) and medium–high (60%) fixed loads, and exhaust particulate was sampled for analysis. The fuels used were ultra-low sulfur diesel and its 20% v/v blends with soybean methyl ester biodiesel. Fuel injection occurred in a single event around top dead center at three different injection pressures. Exhaust particulate samples were characterized with transmission electronic microscopy imaging, scanning mobility particle sizing, thermogravimetric analysis, Raman spectroscopy, and X-ray diffraction analysis. Particulate morphology and oxidative reactivity were found to vary significantly with both rail pressure and biodiesel blend level. Higher biodiesel content led to an increase in the primary particle size and oxidative reactivity but had no impact on nanoscale disorder in the as-received samples. For particulates generated with higher injection pressures, the initial oxidative reactivity increased, but there was no detectable correlation with primary particle size or nanoscale disorder.